STRATEGI PEMASARAN ATP (ANYAMAN TIKAR PURUN) MELALUI MEDIA SOSIAL DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA JELUTUNG II DUSUN SERDANG - Hayuna Hayuna; Mutia Sari; Fildaniyah Fildaniyah; Anggi Saputra; Silawati Silawati; Tania Putri Imelda; Melisa Melisa; Mahrul Mahrul; Mohamad Pajri; Feri Ardiansah (Jurnal Abdimas Bina Bangsa, 2022)
The purpose of this study is to describe marketing strategies that use social media to promote the products being marketed and the buying and selling interactions between sellers and consumers. In the current era, marketing using social media is considered very effective because it makes it easier for consumers and sellers to carry out product buying and selling transactions quickly without meeting face to face. Consumers on social media are more interactive, they can be invited to work together to promote the products they have purchased from sellers so as to expand the marketing network. Through social media, sellers can create innovation and collaboration with consumers in promoting products Based on the results of the research conducted, the marketing strategy of woven mat purun through social media including Facebook, WhatsApp, Instagram by providing interesting pictures and detailed information about the product that accompanies the caption such as product materials, colors, and prices are easy to understand